MOTIVATION AND DISCIPLINE IN RELATION TO WORK PRODUCTIVITY OF LOCAL GOVERNMENT APPARATUS IN PAPUA - Fatem, Agustinus (Bajang Institute, 2025)
This study aims to understand the relationship between motivation and work discipline with the productivity of local government officials in Papua. The background of this study is driven by the reality of low productivity among civil servants, as reflected in the weak effectiveness and efficiency of public services and regional development. The approach used is qualitative with field methods, through observation, in-depth interviews, and documentation to uncover the dynamics of civil servants' behavior in the context of local culture and organizational structure. Analysis is conducted inductively and contextually, with the researcher as the primary instrument. The research results indicate that the low motivation and work discipline of civil servants are caused by various internal and external factors, such as weak leadership, unproductive work culture, co-opted organizational value systems, and inadequate facilities and organizational structures. There are also cliques within the organization and false loyalty to leaders, which undermine commitment to institutional goals. This situation is exacerbated by a politically biased recruitment and promotion system, as well as inadequate work facilities and infrastructure. As a result, employee morale, sense of responsibility, and productivity are low. This study underscores the importance of comprehensive civil service reform in Papua, including improvements to the motivation system, enhanced discipline, and organizational restructuring of the government to make it more professional and results-oriented.